METHODS FOR THE RATIONAL USE OF NATURAL RESOURCES AND THE STUDY OF GEOGRAPHICAL TOURISM IN THE FERGANA VALLEY - Odiljon Tobirov,; Xidoyatkhon Abdinazarova,; Azamjon Jobborov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This review paper examines the methods for the rational use of natural resources and the development of geographical tourism in the Fergana Valley, a region characterized  by  high  ecological  diversity,  rich  cultural  heritage,  and  increasing anthropogenic  pressure.  Based  on  a  comprehensive  analysis  of  interdisciplinary scientific  literature,  the  study  explores  the  interactions  between  natural  resource management,  tourism  development,  and  local  community  involvement.  Particular attention is paid to sustainable tourism concepts, eco-tourism models, and participatory approaches  that  integrate  ecological,  economic,  and  socio-cultural  dimensions.  The findings indicate that rational resource use—especially of water, land, and landscape resources—is a key prerequisite for maintaining environmental balance while ensuring the  long-term  viability  of  the  tourism  sector.  The  review  also  identifies  significant research gaps related to localized environmental impacts of tourism and community perceptions of resource use. The paper concludes that the integration of GIS-based methods,  stakeholder  participation,  and  sustainability  frameworks  is  essential  for formulating  effective  policies  aimed  at  balancing  environmental  conservation  with socio-economic development in the Fergana Valley.